Application of Pana'i Money in Bugis and Non-Bugis Marriages in Wehali Village, Central Malaka District, Malacca Regency - Atika Febryanti Yusuf; Sukardan Aloysius; Darius Mauritius (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is an empirical juridical research conducted in Wehali Village, Central Malacca District, Malacca District. In this study, interviews were conducted with seventeen informants as a guide. The data obtained is then presented in the form of a simple table and analyzed descriptively qualitatively. Based on the research results, it can be concluded that: (1) There are several stages in determining the amount of Uang Pana'i that must be passed in order to reach an agreement between the man and the woman regarding the amount to be paid. (2) There are several factors that affect the amount of Uang Pana'i, including the social status/family position of the prospective bride and groom, the economic condition of the prospective bride, level of education and employment, physical condition, and ethnicity